(untitled) (Journal of Informatics and Mathematical Sciences, 2021)
In this paper, we prove some coincidence and common fixed point theorems for two pairs of weakly compatible mappings satisfying a rational inequality in the framework of complex valued metric spaces. The proved results generalizes and extends some well known results in the literature.